ANALISIS LIMBAH HATCHERY AYAM BROILER SEBAGAI SUMBER PROTEIN PADA PAKAN BENIH IKAN KARPER (Cyprinus carpio) - Sahrul Alim; Dewi Putri Lestari; Romi Sanjaya (Journal of Fish Nutrition, 2026)
Common carp (Cyprinus carpio) is a freshwater aquaculture species with high economic value that requires high-quality feed to support optimal juvenile growth. The utilization of chicken hatchery waste meal as an alternative protein source has the potential to reduce the dependence on fish meal in feed formulations. This study aimed to evaluate the effect of fish meal substitution with chicken hatchery waste meal on the growth performance of common carp juveniles. The experiment was conducted for 50 days from March to May 2024 at the Mataram City Fisheries Service, while proximate analysis of the experimental diets was performed at the Laboratory of Animal Nutrition and Feed Science, Faculty of Animal Science, University of Mataram. A Completely Randomized Design (CRD) consisting of five dietary treatments and three replications was applied. The treatments included fish meal substitution with chicken hatchery waste meal at levels of 0%, 25%, 50%, 75%, and 100%. Juvenile common carp (5–7 cm in length) were stocked at a density of 15 fish per container and fed daily at 3% of total biomass. The observed parameters included specific growth rate (SGR), feed conversion ratio (FCR), feed efficiency (FE), survival rate (SR), and water quality. The results showed that replacing fish meal with chicken hatchery waste meal significantly affected (P < 0.05) the specific growth rate (SGR) and feed efficiency (FE). These findings indicate that chicken hatchery waste meal has considerable potential as an alternative protein source in formulated diets for common carp juveniles.